Temporal Stability and the Effect of Transgenerational Transfer on Fecal Microbiota Structure in a Long Distance Migratory Bird - Kreisinger, Jakub; Kropáčková, Lucie; Petrželková, Adéla; Adámková, Marie; Tomášek, Oldřich; Martin, Jean-François; Michálková, Romana; Albrecht, Tomáš (Frontiers in Microbiology, 2017)
Animal bodies are inhabited by a taxonomically and functionally diverse community of symbiotic and commensal microorganisms. From an ecological and evolutionary perspective, inter-individual variation in host-associated microbiota contributes to physiological and immune system variation. As such, host-associated microbiota may be considered an integral part of the host’s phenotype, serving as a substrate for natural selection. This assumes that host-associated microbiota exhibits high temporal stability, however, and that its composition is shaped by trans-generational transfer or heritable host-associated microbiota modulators encoded by the host genome. Although this concept is widely accepted, its crucial assumptions have rarely been tested in wild vertebrate populations. We performed 16S rRNA metabarcoding on an extensive set of faecal microbiota samples from an insectivorous, long-distance migratory bird, the barn swallow (Hirundo rustica). Our data revealed clear differences in faecal microbiota among juveniles and adults as regards taxonomic and functional composition, diversity and co-occurrence network complexity. Multiple faecal microbiota samples from the same juvenile or adult collected within single breeding seasons exhibited higher similarity than expected by chance, as did adult faecal microbiota samples over two consecutive years. Despite low effect sizes for faecal microbiota stability over time at the community level, we identified an adult faecal microbiota subset with relative abundances exhibiting significant temporal consistency, possibly inducing long-term effects on the host phenotype. Our data also indicate a slight maternal (but not paternal) effect on faecal microbiota composition in social offspring, though this is unlikely to persist into adulthood. We discuss our findings in the context of both evolution and ecology of microbiota vs. host interactions and barn swallow biology.